Hyperphosphataemia after enemas in childhood: prevention and treatment. Issue 2 (February 1993) - Hunter, M F; Ashton, M R; Griffiths, D M; Ilangovan, P; Roberts, J P; Walker, V
Abstract : The case of a child with severe hyperphosphataemia and symptomatic hypocalcaemia secondary to retention of phosphate administered through an antegrade continence enema is reported. Caution should be exercised with the use of phosphate enemas and prompt action taken to remedy retention. The use of glucose with insulin in the emergency management of acute hyperphosphataemia is discussed.